A Letter to Future Physicians: One Dozen Important Things You Might Not Learn Enough about During Medical Training—But Should - Heilig, Steve (Cambridge quarterly of healthcare ethics, 2010)
Medical training is intense by design. Starting with medical school, for 4 years most of the time in the formal curriculum is filled with numerous essential topics, and, as scientific and medical knowledge increases, it is increasingly difficult to “triage” what must be learned. Efforts to insert new topics are often fraught with obstacles and resistance. Thus, it is problematic to suggest that even more be taught in those finite years of formal medical education. However, that is exactly what we propose to do here.